Injectable Capsaicin for the Management of Pain Due to Osteoarthritis - Campbell, James N.; Stevens, Randall; Hanson, Peter; Connolly, James; Meske, Diana S.; Chung, Man-Kyo; Lascelles, Benedict Duncan X. (Molecules (Basel, Switzerland), 2021)
Capsaicin is a potent agonist of the TRPV1 channel, a transduction channel that is highly expressed in nociceptive fibers (pain fibers) throughout the peripheral nervous system. Given the importance of TRPV1 as one of several transduction channels in nociceptive fibers, much research has been focused on the potential therapeutic benefits of using TRPV1 antagonists for the management of pain. However, an antagonist has two limitations. First, an antagonist in principle generally only affects one receptor. Secondly, most antagonists must have an ongoing presence on the receptor to have an effect. Capsaicin overcomes both liabilities by disrupting peripheral terminals of nociceptive fibers that express TRPV1, and thereby affects all of the potential means of activating that pain fiber (not just TRPV1 function). This disruptive effect is dependent on the dose and can occur within minutes. Thus, unlike a typical receptor antagonist, continued bioavailability at the level of the receptor is not necessary. By disrupting the entire terminal of the TRPV1-expressing nociceptive fiber, capsaicin blocks all the activation mechanisms within that fiber, and not just TRPV1 function. Topical capsaicin, an FDA approved treatment for neuropathic pain, addresses pain from abnormal nociceptor activity in the superficial layers of the skin. Effects after a single administration are evident over a period of weeks to months, but in time are fully reversible. This review focuses on the rationale for using capsaicin by injection for painful conditions such as osteoarthritis (OA) and provides an update on studies completed to date.